Study on the microcosmic superlubricity mechanism of PVPA affected by metal cations - Hongyun Cai; Caixia Zhang; Fuping Li; Mengmeng Liu; Tao Zhang; Hongyan Chu; Zhifeng Liu (Friction, 2022)
Abstract Hydrophilic polymer coatings on artificial implants generate excellent tribological properties. The friction properties of polymer coatings are affected by salt ion factors. Herein, the atomic force microscopy (AFM) was used to show that the superlubricity was achieved between poly(vinylphosphonic acid) (PVPA)-modified Ti6Al4V and polystyrene (PS) microsphere probe lubricated with monovalent salt solutions (LiCl, NaCl, KCl, and CsCl). Considering that adhesion is an important cause of friction changes, the AFM was further utilized to obtain adhesion between friction pairs in different salt solutions. The results indicated that the larger the cation radius in the lubricant, the smaller the adhesion, and the lower the friction coefficient of the PVPA coating. The electrostatic interaction between the PVPA and one-valence cations in lubricants was analyzed by the molecular dynamics (MD) simulation as it was found to be the main influencing factor of the adhesion. Combined analysis results of friction and adhesion indicated that by adjusting the size of cation radius in lubricant, the adhesion between the tribo-pairs can be changed, and eventually the magnitude of friction can be affected. This study opens up a new avenue for analyzing the friction characteristics of hydrophilic polymer coatings from the perspective of intermolecular forces.